As(III) removal under the presence of competitive anions using the calcined ground oyster shell as the adsorbent - Khownpurk, P.; Chandra-Ambhorn, W. (My University, 2020)
The calcined ground oyster shell was used as the adsorbent to remove As(III) from contaminated water under the presence of anions. The solubility and precipitation tests indicated that As(III), NO3 −, and SO4 2- were removed by adsorption process whereas HPO4 2- was removed by precipitation and adsorption processes. The adsorption results showed that, in bi-solutes, HPO4 2- strongly interfered with As(III) removal. In the case of tri- and tetra-solutes, the adsorption performances of As(III) and anions depended on (1) the binding affinity between the sorption sites and adsorbates, (2) observed adsorption rate constant of adsorbates, (3) electrostatic interaction, and (4) adsorbates interaction.
Keywords: adsorption; adsorption kinetics; Arsenic removal; calcined ground oyster shell; competitive anion